Common Bantoid Verb Extensions - Hyman, Larry (My University, 2018)
In this paper I survey verb extensions within different Bantoid languages and sub-groups, comparing them to Cameroonian Bantu zone A. Extending my survey of Niger-Congo extensions (Hyman 2007), I show that there is a band of contiguous languages in the Grassfields area where a number of contrastive verb extensions have relative productivity (cf. the studies in Idiata & Mba 2003). Interestingly, the languages in question belong to several subgroups: Limbum (NE Eastern Grassfields Bantu), Noni (Beboid), Kom and Babanki (Ring Western Grassfields Bantu), Bafut and Mankon (Ngemba Eastern Grassfields Bantu). Other languages in these same subgroups are not in this geographical band and have very few extensions. The above-mentioned languages allow a possible reconstruction of *CV extensions with *s, *t, *n, *l, *k, and *m. A major property of Bantoid extensions is the relative frequency of aspectual-type extensions, especially marking different types of pluractionality (iterative, frequentative, distributive, repetitive), diminutive (attenuation of action), and intensive (augmentation of action) semantics. In many languages the same suffix form covers two or more of these functions. The hypothesis is that the original system was more like Proto-Bantu, with extensions being more valence-related, but over time these very same extensions became reinterpreted as aspectual. However, the great variety of extensions in and outside of Bantoid suggests that there may have been more extensions at a pre-Proto-Bantu stage.
Keywords: Bantoid languages; Bantoid verb extensions; Niger-Congo extensions